1993
DOI: 10.1227/00006123-199303000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation Excites the Root Exit Zone of the Facial Nerve

Abstract: The actual site of excitation of the facial nerve by transcranial magnetic stimulation was investigated in five patients with hemifacial spasm who underwent microvascular decompression. The facial nerve was stimulated preoperatively and intraoperatively by transcranial magnetic stimulation and intraoperatively by electrical stimulation at its root exit zone with a minimum of surgical invasion of the facial nerves. The onset latency of compound muscle action potentials recorded from the nasalis muscle was 5.06 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…There is some evidence that when using transcranial magnetic stimulation the peripheral seventh nerve is stimulated directly without conduction through the central motor pathway from the cortex (17,(19)(20)(21). C3-C4 stimulation always caused bilateral facial MEP responses; the side of dorsal interosseous and tibialis anterior MEP responses were dependent on the current direction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is some evidence that when using transcranial magnetic stimulation the peripheral seventh nerve is stimulated directly without conduction through the central motor pathway from the cortex (17,(19)(20)(21). C3-C4 stimulation always caused bilateral facial MEP responses; the side of dorsal interosseous and tibialis anterior MEP responses were dependent on the current direction.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been found that the latency in transcranial magnetic stimulation of peripheral facial nerve responses was approximately 5 milliseconds (17,(19)(20)(21). This corresponds to the latency of the recorded ipsilateral facial CMAP cause by a single-pulse stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmid et al [16] suggested that the short-latency response results from stimulation of the facial nerve in its intracisternal part, presumably 10 mm after its entrance into the stylomastoid foramen. Tokimura et al [19] described stimulation at the root entry zone and therefore assumed an investigation benefit of TMS in cerebellopontine angle tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, scientists and clinicians began focusing on the evolution and possible clinical applications of the transcranial magnetic stimulation system in facial nerve disorders. 2,3,16–28 …”
Section: Introductionmentioning
confidence: 99%